LAND SUBSIDENCE MONITORING AND ANALYSIS IN FUZHOU BASED ON INSAR AND MULTISPECTRAL REMOTE SENSING TECHNOLOGY - Y. Y. Zhu; Y. F. He; Y. F. He; H. Y. Li; Z. P. Lv; Z. P. Lv; G. C. Xu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Interferometric Synthetic Aperture Radar (InSAR) technology has millimeter level measurement accuracy and has great advantages in urban land subsidence monitoring. Meanwhile, multispectral remote sensing technique can also provide a large amount of urban features changes information for analyzing the causes of land subsidence. In this study, SAR and multispectral images are both used to monitor and analyze land subsidence in Fuzhou of China. 115 scenes Sentinel-1 SAR images from May 2017 to May 2021 are used based on the Persistent Scatterers Interferometric (PSI) method to evaluate the land subsidence in Fuzhou, while Sentinel-2 multispectral images are used to evaluate several remote sensing indexes. During SAR data processing, Generic Atmospheric Correction Online Service for InSAR (GACOS) data is used to remove atmospheric errors for higher accuracy land subsidence. In order to analyze the relationship between the land subsidence and land cover changes in urban areas, the Soil-Adjusted Vegetation Index (SAVI), Normalized Difference Built-up Index (NDBI) and Modified Normalized Difference Water Index (MNDWI) of the main subsidence areas are obtained based on Sentinel-2 multispectral images from 2016 to 2021. In the end, it is found that the land subsidence in some areas exceeded 12 mm/year in Fuzhou. The time series of four areas with severe subsidence were analyzed, and the cumulative subsidence reached about 60 mm. Besides, the spatial distribution and temporal changes of vegetation, buildings and water bodies in these areas were obtained based on the multispectral data, it is found there is very less relationship between the land subsidence and the urban features. It is concluded that that the main causes of the land subsidence are the changes of land internal components such as groundwater and others.